Listeriosis in pregnancy: a challenge in diagnosis - Basri, Nurul Iftida (BMJ Publishing Group, 2024)
Listeriosis is a rare foodborne infection caused by Listeria monocytogenes. It has been reported to be commonly found among the obstetric population, immunocompromised group and elderly, presumably due to the lower immunity status in these populations. Presentation in pregnancy is usually non-specific like fever, diarrhoea, respiratory tract symptoms and preterm rupture of membrane. These make the diagnosis challenging and may delay the correct management. We present a case of a female in her early 40s, gravida 4 para 0+3 at 27 weeks who presented with fever. She later developed preterm rupture of membrane 24 hours after admission. The leaking of liquor later changed from clear to meconium stained raising the suspicion of listeria chorioamnionitis, necessitating an emergency preterm delivery via caesarean section. The newborn acquired listeria infection and required ventilation support. He subsequently was discharged from neonatal unit after nearly 3 months of life.